S182. HISTONE H3 AND H4 POST-TRANSLATIONAL REGULATION IN SCHIZOPHRENIA POSTMORTEM BRAIN: EFFECT OF ANTIPSYCHOTIC TREATMENT - Martínez-Peula, Oihane (Schizophr Bull, 2020)
BACKGROUND: Epigenetic modifications recording obstetrical adverse events are a fundamental component of the neurodevelopmental hypothesis of schizophrenia (SZ). Epigenome-wide association studies performed in peripheral tissues samples of first-episode cases or young population at high risk of SZ lack from brain tissue specificity. Unfortunately, with the current technology, brain epigenetic mechanisms can only be assessed postmortem, difficulting the separation of illness-specific features from confounding factors, such as medication intake. Besides, most postmortem brain studies focused in gene-specific epigenetic alterations, with few studies reporting findings on the overall load of epigenetic modifications. Here, we mapped the most common post-translational modifications (PTM) occurring at histone level (H3 and H4) in a well-characterized case-control cohort, large enough to address the effects of most typical confounders in postmortem brain studies. METHODS: Dorsolateral prefrontal cortex (DLPFC) samples from SZ subjects (n=22) and sex-, age- and postmortem interval- (PMI) matched controls (n=22) were obtained at autopsies in the Basque Institute of Legal Medicine. Medical and toxicological reports were obtained as part of the forensic investigations. Cases with DSM-IV-based SZ diagnoses were selected, excluding those with neurological or psychiatric conditions, or those presenting drugs of abuse in blood samples. Blood toxicology also allowed the separation between antipsychotic drug (APD) treated (n=10) from APD-free (n=12) cases. Cortical levels of repressing (trimethylated H3 at Lys27 [H3K27me3] and H4 at Lys20 [H4K20me3]) and activating (trimethylated H3 at Lys4 [H3K4me3], acetylated H3 at Lys9 [AcH3K9] and Lys27 [AcH3K27], and acetylated H4 at Lys16 [AcH4K16]) histone H3 and H4 protein species were quantified by Western blotting using selective antibodies. RESULTS: DLPFC expression levels of total forms of histone H3 and H4 proteins did not differ between SZ subjects and controls. However, SZ was associated with a significant upregulation of the histone H3 activating mark AcH3K9 (+32%, p<0.05). Both APD-free and APD-treated cases showed similar alterations on this H3 PTM. AcH3K9 upregulation was not driven by any of the confounders evaluated, including sex, age, PMI, suicide, or the presence of alcohol or other psychoactive drugs in blood samples. All other gene activating and repressing epigenetic marks studied at histones H3 and H4 remained unchanged in SZ brains, compared to controls. DISCUSSION: Upregulated cortical AcH3K9 levels may be associated with overall, unspecific increase of gene expression in SZ cortical cells. Notably, AcH3K9 modulation seems an illness specific epigenetic signature, as medication or other confounders had no impact on AcH3K9 amounts. Future research will focus on the cell specificity of this finding, which might provide new clues toward future interventions at the molecular level in SZ.